PENERAPAN MODEL PEMBELAJARAN KOOPERATIVE GROUP INVESTIGATION (GI) BERBANTUAN QUIZZIZ UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA PADA PEMBELAJARAN IPAS KELAS V UPTD SD NEGERI 04 SULIKI - Mena Lestari; Kms. Muhammad Amin Fauzi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine whether the application of the cooperative learning model group investigation can improve students' learning motivation in science learning for grade V. The research method used in this study is the Pre Experimental design. Pre experimental research uses a one group pretest posttest design. The sample in this study used the random sampling technique. The sample used was 9 students of grade 5 of UPTD SD Negeri 04 Suliki. The results of the study showed a p value = 0.000 (p <0.05), where there was a significant difference between the pretest and posttest scores. This proves that the quizziz-assisted group investigation model can improve students' learning motivation. Keywords: group investigation, motivation, quizziz